Makna Penggunaan Gaya Bahasa Ironi dalam Narasi Hakim-Hakim 4:1-24 - Giyarto Giyarto; Daniel Lindung Adiatma (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2020)
The book of judges is an important historical theological book in Old Testament Canon. This book uses narrative literature as common narrative books in Old Testament. Judges 4:1-24 is part of narrative book of Judges. Some interpretation books do not pay attention to literary approach. Especially on Judges 4:1-24 some interpretation only concern to Deborah dan Barak and their success. Irony is one of the language styles used in describing a narrative. This article aims to examine the meaning of the use of irony in the narrative of Judges 4: 1-24. Through narrative literary research and the use of irony in language, the interpreters discover the theological meanings that contained in the narrative of Israel's deliverance of the oppression. Abstrak Kitab Hakim-Hakim merupakan kitab sejarah teologis yang penting dalam kanon Perjanjian Lama yang memakai sastra narasi. Tidak banyak buku tafsir yang memeriksa penggunakan unsur sastra dalam menafsirkan kitab Hakim-Hakim 4:1-24. Ironi adalah salah satu gaya bahasa yang dipakai dalam melukiskan narasi. Artikel ini bertujuan meneliti makna penggunaan gaya bahasa ironi dalam narasi Hakim-Hakim 4:1-24. Melalui penelitian sastra narasi dan penggunaan gaya bahasa ironi, penafsir menemukan kekayaan makna teologis yang terkandung dalam narasi pembebasan Israel dari penindasan raja Kanaan.